2000
DOI: 10.1021/bi001574j
|View full text |Cite
|
Sign up to set email alerts
|

Polar Group Burial Contributes More to Protein Stability than Nonpolar Group Burial

Abstract: On the basis of studies of Asn to Ala mutants, the gain in stability from burying amide groups that are hydrogen bonded to peptide groups is 80 cal/(mol A(3)). On the basis of similar studies of Leu to Ala and Ile to Val mutants, the gain in stability from burying -CH(2)- groups is 50 cal/(mol A(3)). Thus, the burial of an amide group contributes more to protein stability than the burial of an equivalent volume of -CH(2)- groups. Applying these results to folded proteins leads to the surprising conclusion that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 29 publications
6
121
0
Order By: Relevance
“…The hRI·RNase 1 complex also buries an additional 375 Å 2 of surface area, which could also enhance its stability. 48,45,49 In line with the more intimate complex formed by hRI and RNase 1, RNase 1 dissociates from hRI 150-fold more slowly than does RNase A from hRI ( Figure 5 ; Table 3). 12 The slower dissociation rate (t ½ = 81 days) for the hRI·RNase 1 complex is in the range of that for the hRI·angiogenin complex (t ½ = 62 days).…”
Section: Recognition Of Rnase 1 By Rimentioning
confidence: 80%
See 1 more Smart Citation
“…The hRI·RNase 1 complex also buries an additional 375 Å 2 of surface area, which could also enhance its stability. 48,45,49 In line with the more intimate complex formed by hRI and RNase 1, RNase 1 dissociates from hRI 150-fold more slowly than does RNase A from hRI ( Figure 5 ; Table 3). 12 The slower dissociation rate (t ½ = 81 days) for the hRI·RNase 1 complex is in the range of that for the hRI·angiogenin complex (t ½ = 62 days).…”
Section: Recognition Of Rnase 1 By Rimentioning
confidence: 80%
“…[43][44][45][46] Hydrogen bonds between functional groups of opposite charge (i.e., salt bridges) are especially strong. 47 Overall, the hRI·RNase 1 complex has both more intermolecular hydrogen bonds than does the pRI·RNase A complex and more between residues of opposite charge (Table 2).…”
Section: Recognition Of Rnase 1 By Rimentioning
confidence: 99%
“…The theoretical studies that reach different conclusions need to be re-examined. We have emphasized previously the importance of van der Waals interactions in the tightly packed interior of a protein to the contribution of polar group burial to stability (4). Recently, several groups have pointed out that the enhanced van der Waals interactions resulting from the tight packing of groups in the interior of folded proteins are also of crucial importance to the hydrophobic effect (24,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…We recently suggested that polar group burial makes a larger contribution to the stability of globular proteins than nonpolar group burial (4). This idea is supported by most experimental studies (5-11), but not by most theoretical studies (12)(13)(14).…”
mentioning
confidence: 97%
“…The formation of secondary structure effectively buries hydrogen bonds, which further decreases the free energy of the emergent protein. In fact, burial of hydrogen bonds or polar groups in the hydrophobic core of a protein contributes more to overall stability than burial of the volume equivalent of non-polar groups [2,3]. As folding progresses, the secondary structure elements are assembled into native-like tertiary structures, where the exclusion of water due to tight packing of the structural elements further decreases the free energy of the nascent protein as it descends through the energy landscape towards its native structure.…”
Section: Tertiary Structure -Hold the Foldmentioning
confidence: 99%